Factors Associated with Functional Well-Being and Psychological Parameters among Cancer Patients Receiving Chemotherapy Admitted to a Select Cancer Hospital in Bagalkot District - An Exploratory Study - Shilpa N Kugali; Deelip S Natekar; Mahesh Wangi (RGUHS Journal of Nursing Sciences)
Background The global burden of cancer was estimated to have increased to 18.1 million new cases and 9.6 million deaths in 2018. One in 10 men and one in 10 women will develop cancer and a similar proportion will die from it. Approximately 43.8 million people worldwide are surviving within five years of their cancer diagnosis known as the five-year survival rate. The increase in cancer incidence could be attributed to many factors including population growth aging and changes in some health and economic conditions related to cancer.Method The research approach adopted in this present study was quantitative non-experimental approach and the research design adopted was descriptive cross sectional explorative design. Fifty subjects with cancer who were receiving chemotherapy at the select hospital in Bagalkot were selected using disproportionate stratified random sampling technique. A structured questionnaire was developed to collect the demographic information and to assess the level of functional wellbeing stress and anxiety. Stress was measured using Cohenrsquos perceived stress scale. The degree of anxiety was measured with Zung self-rating anxiety scale SAS. The data collected were analyzed using descriptive and inferential statistics.Results Cancer patients level of understanding of cancer showed that most patients 40 had a positive life experience 20 had a good life experience quality of life and 40 had a bad life experience quality of life. Stress levels of cancer patients showed that most patients experienced high stress 58 28 patients experienced slightly high stress and 14 experienced low stress. About 40 reported to have experienced mild to moderate anxiety 30 reported mild to severe anxiety 24 experienced severe anxiety and 6 reported more than one level of anxiety. Conclusion A significant relationship between health and its psychological and social variables was noted. As a result cancer patients experience significant levels of stress anxiety and health disorders while receiving chemotherapy.nbsp